Efectos de fertilizante edáfico y foliar en el comportamiento agronómico del pasto Mombasa (Panicum máximum Jacq cv Mombasa) en el Cantón Babahoyo, Provincia de Los Ríos - Alvarado Medina, Mercedes Rosario (2020)
The present work was carried out with the purpose of analyzing the agronomic behavior of the Mombasa grass (Panicum maximum Jacq. Cv Mombasa) by applying edaphic plus foliar fertilization in the Babahoyo area with four treatments, two edaphic and two foliar, because grasses are very important in terrestrial ecosystems since they have always existed, they have adapted in different environments serving as the main food for animals and in Babahoyo canton in one of the most important pastures in livestock farms, where it is mainly used like grazing and cutting. A vegetative development of the progressive pasture was observed as a function of the increase in the dose of fertilizers, yields of 2,106.3 and 2,748.0 Kg / ha / cut being found between the control and the treatment with the highest dose of fertilization, which shows that the Supplementation of soil nutrient deficiencies with soil or foliar fertilization provides excellent results for pasture species or varieties in the region.